Casson Fluid Flow Past a Patient-Specific Atherosclerotic Artery under External Magnetic Field - Ikbal, Md. Asif (Journal of Applied Nonlinear Dynamics, 2026)
Mathematical modelling of blood flow through a patient-specific atherosclerotic artery has been developed in the present study. The blood flow within the arterial lumen is assumed to behave as a non-Newtonian Casson fluid. An external transverse magnetic field is applied to the flowing blood. The nonlinear coupled governing equations, along with the relevant initial and boundary conditions, are solved numerically using the MAC (Marker and Cell) method, satisfying suitable stability criteria. The effects of the external magnetic field (Hartmann number) on the axial velocity, wall shear stress, and pressure are shown graphically. Significant effects of Reynolds number and yield stress on both axial velocity and wall shear stress have also been observed. The present study also investigates the significant effect on the velocity profile in the presence of an external magnetic field. The simulated results indicate that the dimensionless centreline velocity is higher for the Newtonian model compared to its non-Newtonian counterpart. The predicted results agree well with the results available in the literature.